Enterovirus A71 VP1 Variation A289T Decreases the Central Nervous System Infectivity via Attenuation of Interactions between VP1 and Vimentin In Vitro and In Vivo - Huimin Zhu; Yujuan Cao; Weitao Su; Shan Huang; Weizhi Lu; Yezhen Zhou; Jing Gao; Wei Zhao; Bao Zhang; Xianbo Wu (Viruses, 2019)
Vimentin (VIM) is a surface receptor for enterovirus-A71, mediating the initial binding and subsequent increase in EV-A71 infectivity. The caspid protein VP1 variation, A289T, is reportedly closely associated with less severe central nervous system (CNS) infections in humans. However, it is unclear whether VIM is associated with a reduction in CNS infections of EV-A71 in the presence of A289T. We investigated whether VIM served as a receptor for EV-A71 in the presence of an A298T substitution in VP1. EV-A71-289A and EV-A71-289T were used to infect human rhabdomyosarcoma cells, control human brain microvascular endothelial cells (HBMECs), and VIM-knockout (KO) HBMECs and inoculated BALB/c mice, SV129 mice, and VIM-KO SV129 mice. Furthermore, we cloned VP1-289A-Flag and VP1-289T-Flag proteins for co-immunoprecipitation analysis. Analysis of viral function revealed that the capacity of viral attachment, replication, and protein synthesis and secretion decreased in HBMECs during an EV-A71-289A infection, the infectivity being higher than that of EV-A71-289T upon VIM-KO. Histopathological and immunohistochemical analyses of brain tissue revealed that cerebral cortical damage was more extensive in EV-A71-289A than in EV-A71-289T infections in control SV129 mice; however, no significant difference was observed upon VIM-KO. Co-immunoprecipitation analysis revealed an interaction between VP1 and VIM, which was attenuated in VP1 harboring A289T; however, this attenuation was reversed by VIM (1-58) peptide. The A289T variation of VP1 specifically decreased the virulence of EV-A71 in HBMECs, and the attenuated interaction between VP1 harboring the A289T variation and VIM essentially decreased the CNS infectivity of EV-A71 in vitro and vivo.